Program KKN di Kecamatan Batang Alai Utara Kabupaten Hulu Sungai Tengah Mahasiswa UIN Antasari Pasca Covid pada KKN Semester Genap 2021-2022 - Norlaila Norlaila; Siti Zahroo; Ahmad Firdaus (UIN Antasari Banjarmasin, 2022)
AbstractKKN or Real Work Lectures is one of the community services carried out by tertiary institutions as their duty to carry out their Tridhama. In particular, UIN Antasari carries out KKN activities every semester. The aim is to direct students to become facilitators, motivators, catalysts and innovators in society. UIN antasari directs KKN to villages in South Kalimantan and its surroundings, where students are able to develop their knowledge and experience in the community with various appropriate programs in their respective regions related to religion, village administration and cross-sectoral. UIN Antasari in the 2022 Even Semester KKN fielded students in several areas in the HSS, HST, HSU and Tanah Bumbu Regencies. KKN was carried out for one and a half months, from April 14 to May 25, 2022. There are a number of issues that KKN students hope for during this period, bearing in mind that the implementation is in the Month of Ramadhan, where learning in educational institutions is during the holidays, and then the habits of the people who rest more at home to carry out fasting, and post-covid which just ended. Thus, KKN students seek to develop work program plans that are appropriate to the situation and circumstances. By discussing with Supervisors and having dialogue with the Village Head and the community, KKN students in the BAU Subdistrict have succeeded in carrying out several memorable KKN programs in the BAU Subdistrict community. Among the programs are Teaching and Motivating Learning and Reading and Writing the Qur'an and introducing the Tilawati Model, other religious programs, socialization of gender equality and gender relations, socialization of early marriage, socialization of understanding and awareness of success and waste management, as well as cross-sectoral and administrative activities.AbstrakKKN atau Kuliah Kerja Nyata merupakan salah satu pengabdian masyarakat yang dilaksanakan oleh Perguruan Tinggi sebagai tugasnya dalam melakanakan Tridhamanya. Khususnya UIN Antasari melaksanakan kegiatan KKN pada setiap semesternya. Tujuannya untuk mengarahkan mahasiswa agar menjadi fasilitator, motivator, katalisator serta innovator di masyarakat. UIN antasari mengarahkan KKN ke desa-desa di Kalimantan Selatan dan Sekitarnya, di mana agar mahasiswa mampu mengembangkan keilmuan dan pengalamannya di masyarakat dengan berbagai program yang sesuai di daerah masing-masing terkait dengan keagamaan, administrasi desa serta lintas sektoral. UIN Antasari pada KKN Semester Genap 2022 menerjunkan mahasiswa di beberapa daerah di Kabupaten HSS, HST, HSU dan Tanah Bumbu. KKN silaksanakan selama satu bulan setengah, dari tanggal 14 April sampai dengan 25 Mei 2022. Ada beberapa persoalan yang diharapi mahasiswa KKN pada periode ini, mengingat pelaksanaanya di Bulan Romadhan, di mana pembelajaran lembaga-lembaga pendidikan dalam masa liburan, dan kemudian kebiasaan masyarakat yang lebih banyak beristirahat di rumah untuk melaksanakan puasa, dan pasca kovid yang baru saja berakhir. Dengan demikian, mahasiswa KKN berupaya untuk menyusun rencana program kerja yang sesuai dengan situasi dan keadaan. Dengan berdiskusi bersama dengan Supervisor dan berdialog dengan Kepala Desa serta masyarakat, mahasiswa KKN di Kecamatan BAU berhasil melaksanakan beberapa program KKN yang berkesan di masyarakat Kecamatan BAU. Di antara program adalah Mengajar dan Memotivasi Pembelajadan Baca Tulis Al-Qur’an serta mengenalkan Model Tilawati, program keagamaan lainnya, sosialisasi kesetaraan gender dan relasi gender, sosialisasi pernikahan dini, sosialisasi pemahaman dan kesadaran keberhasilan dan pengelolaan sampah, serta kegiatan administarasi derta lintas sektoral.